2019
DOI: 10.1016/j.bja.2019.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative anaemia with cardiopulmonary exercise capacity and postoperative outcomes in noncardiac surgery: a substudy of the Measurement of Exercise Tolerance before Surgery (METS) Study

Abstract: Background: Preoperative anaemia is associated with elevated risks of postoperative complications. This association may be explained by confounding related to poor cardiopulmonary fitness. We conducted a pre-specified substudy of the Measurement of Exercise Tolerance before Surgery (METS) study to examine the associations of preoperative haemoglobin concentration with preoperative cardiopulmonary exercise testing performance (peak oxygen consumption, anaerobic threshold) and postoperative complications. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Our patient's comorbidities included iron deficiency anaemia. Anaemia is associated with poor cardiorespiratory fitness, but recent international studies have concluded that the contribution of anaemia to reduced exercise capacity is small [8]. Iron deficiency itself is also associated with reduced exercise capacity owing to its role in oxygen delivery and cellular respiration, however, studies in athletes have demonstrated that intravenous iron transfusion does not lead to increased aerobic capacity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's comorbidities included iron deficiency anaemia. Anaemia is associated with poor cardiorespiratory fitness, but recent international studies have concluded that the contribution of anaemia to reduced exercise capacity is small [8]. Iron deficiency itself is also associated with reduced exercise capacity owing to its role in oxygen delivery and cellular respiration, however, studies in athletes have demonstrated that intravenous iron transfusion does not lead to increased aerobic capacity [9].…”
Section: Discussionmentioning
confidence: 99%
“…During this process, patients will pedal at a speed of 60 rotations per min. Typically, untrained individuals increase their productivity by 10 watts per min, while participants who regularly participate in sports activities increase their productivity by 20 to 30 watts per min [ 23 , 24 ]. The main recorded indicators are, peak oxygen consumption (VO 2peak ), and anaerobic threshold.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies [ 27 , 28 ], it is estimated that the incidence of postoperative cardiopulmonary exercise capacity declines in elderly patients, with intermediate or high risk of 30% to 45%. Based on these reports and the results of a preliminary trial, we assume that titration of iPEEP will reduce the decline of postoperative cardiopulmonary exercise capacity by 50% of fixed PEEP.…”
Section: Methodsmentioning
confidence: 99%
“…The association between low functional capacity and increased morbidity and mortality is robust [6,7], however, evidence for a clear cut-off value is lacking. Therefore, all current guidelines use 4 MET as the cut-off for the definition of low functional capacity.…”
Section: Determination Of Functional Capacitymentioning
confidence: 99%